Decoding Social Standards for Children: A Case Study of Banjarese Songs - Ninuk Krismanti (Master Program in Linguistics, Diponegoro University, 2020)
This study is set to explain social standards decoded through traditional songs for Banjarese children. This study is carried out under a descriptive qualitative design. The data are taken from 36 songs sung for different purposes, from lullabies to traditional games companions. Observation and interviews are the techniques employed to collect the data. The observation and the interview are conducted in regions representing two distinguished dialects of the Banjar language: Banjar Hulu and Banjar Kuala. Cultural Linguistics is an approach for data analysis. The lyrics of investigated songs are registered into five categories reflecting different standards expected by Banjarese society for children. The results of the study show the desired and undesired social values believed by Banjarese society. These values are introduced to children, not through the media of preaching, but common practice of Banjarese families, singing.